Rapid review of drug management for paediatric seizure termination in the emergency setting - Stockigt, Jeannie Claudette (Division of Emergency Medicine, 2016)
Prolonged seizures are a medical emergency and require immediate treatment to prevent complications. Benzodiazepines (BDZ's) are integral to acute seizure management. The most commonly used BDZs are Lorazepam, Diazepam and Midazolam. Lorazepam is often perceived as the superior choice but recent studies have challenged this but results appear inconclusive and contradictory. This study aims to consolidate the available literature and formulate recommendations for the use of BDZs in the emergency setting for children. Methods A rapid review methodology with a tiered approach was used. This approach uses high quality guidelines as the first tier, review of reviews (second tier) then systematic reviews and the fourth and final tier uses randomized control trials as primary data. The Australian National Health Medical Research Council's matrix for grading and developing guidelines was used to grade quality of recommendations.